ARDUINO-ENHANCED RUBU' AL-MUJAYYAB INTEGRATIVE LEARNING MODEL FOR MATHEMATICAL PROBLEM-SOLVING ABILITY - Hidayat, Muhammad; Akrim, Akrim; Arifin, Muhammad (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Mathematical problem-solving ability among Indonesian students, particularly in Islamic-based secondary schools, remains low, partly because classroom instruction rarely connects trigonometry to the scientific heritage of Islamic civilization. This study aimed to develop and evaluate an Integrative Learning Model based on Rubu' Al-Mujayyab Media (ILM-RAM), a digitally enhanced quarter-circle astronomical instrument integrated with problem-based learning and ethnomathematics, to improve students' mathematical problem-solving ability. This study used a Research and Development approach with the ADDIE model, producing a teacher guidebook, student textbook, student activity sheets, lesson plans, and an Arduino-enhanced Rubu' Al-Mujayyab instrument, which were tested in two field trials involving Grade X students at a Muhammadiyah senior high school in North Sumatra, Indonesia (n = 26 per trial). Data were collected through expert validation sheets, teaching-management observation, student response questionnaires, and problem-solving tests, then analyzed using product-moment validity, Cronbach's Alpha reliability, and normalized N-Gain. The learning devices and instruments were rated valid by five experts (mean scores 4.06–4.26 of 5), with very high item validity (r = 0.82–0.98) and good reliability. After revision following the first trial (69% classical mastery; below 80% positive response on most aspects), the second trial showed strong practicality (teacher-management score 4.08, "good" category; 87–100% positive student response) and high effectiveness (88.5% classical mastery; mean N-Gain = 0.60, medium category). The novelty of this study lies in operationalizing classical Islamic scientific heritage as a functional, technology-based pedagogical medium within a systematically validated integrative model, rather than merely as a symbolic cultural reference.